2006
DOI: 10.1667/rr0588.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Learning and Memory Deficits after Whole-Brain Irradiation are Associated with Changes in NMDA Receptor Subunits in the Hippocampus

Abstract: Whole-brain irradiation is used for the treatment of brain tumors, but can it also induce neural changes, with progressive dementia occurring in 20-50% of long-term survivors. The present study investigated whether 45 Gy of whole-brain irradiation delivered to 12-month-old Fischer 344 x Brown Norway rats as nine fractions over 4.5 weeks leads to impaired Morris water maze (MWM) performance 12 months later. Compared to sham-irradiated rats, the irradiated rats demonstrated impaired MWM performance. The relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
112
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(124 citation statements)
references
References 67 publications
9
112
1
Order By: Relevance
“…Although a limited number of neurons died following radiation, the dysfunction in axons and synapses may induce central nervous system damage (28). In addition, radiation may eliminate oligodendrocytes (29), resulting in a decrease in GM volume.…”
Section: Mni Coordinate (Mm) ----------------------------------mentioning
confidence: 99%
“…Although a limited number of neurons died following radiation, the dysfunction in axons and synapses may induce central nervous system damage (28). In addition, radiation may eliminate oligodendrocytes (29), resulting in a decrease in GM volume.…”
Section: Mni Coordinate (Mm) ----------------------------------mentioning
confidence: 99%
“…Shi et al 24 found that the relative levels of certain subtypes of the N-methyl D-aspartate receptor were significantly higher in the hippocampal cornu ammonis 1 (CA1) region of irradiated rats compared with control rats after whole-brain radiation, indicating a possible involvement of an altered glutamate neurotransmission and/or excitatory neurotoxicity in radiation-induced cognitive impairments. Other mechanisms, such as the death of parenchymal and vascular cells, and even the inhibition of the formation of new neurons in the hippocampus, could also be involved.…”
Section: Figmentioning
confidence: 99%
“…As a result, up to 50% of patients who survive long term after treatment experience progressive dementia, thus severely compromising quality of life . The available experimental data clearly demonstrate that radiation also leads to a progressive impairment of cognitive function in animal models, mimicking the clinical scenario of cognitive decline in patients after WBI (Lamproglou et al 2001;Shi et al 2006;Soussain et al 2009;Warrington et al 2012;Welzel et al 2008aWelzel et al , 2008b. Recent studies show that in addition to its profound harmful effects on cognitive function, WBI can also result in the impairment of other brain functions such as coordination of gait (Hatcher-Martin and Factor 2016).…”
mentioning
confidence: 91%